Hate in the time of coronavirus: exploring the impact of the COVID-19 pandemic on violent extremism and terrorism in the West - Marone, Francesco (Secur J, 2021)
Novel COVID-19 is having far-reaching consequences worldwide. Security and security management are not immune from this influence. Building on the scientific literature, this article explores the mixed impact of this unexpected macro-level phenomenon and its consequences on violent extremism and terrorism in the West, in the short and in the medium to long term. The paper looks at the influence on extremist beliefs and attitudes and, moreover, it examines the effects on extremist behaviors, with an emphasis on terrorist activities, drawing on a model of terrorist attack cycle. The COVID-19 pandemic can be interpreted as a global natural experiment that offers insight into causal processes, in the interplay among societal, group, and individual factors.